A Measurement System to Monitor Propulsion Performance and Ice-Induced Shaftline Dynamic Response of Icebreakers - Alessandro Zambon; Lorenzo Moro; Jeffrey Brown; Allison Kennedy; Dan Oldford (Journal of Marine Science and Engineering, 2022)
Polar navigation entails challenges that affect the continuation of ship operations in severe ice conditions. Due to ice-propeller interaction, propulsion shafting segments are often at a high risk of failure. Efficient methods for shaft line design are hence needed to ensure the safety of ice-going vessels and propulsion reliability. To this end, full-scale measurements have proven essential to support the development of ship-design tools and updated safety regulations for ice-going vessels. This paper presents a unique integrated measurement system that employs measuring equipment to monitor Polar-Class vessel performance and shaft line dynamics during ice navigation. The system was installed on board the Canadian Coast Guard (CCG) icebreaker Henry Larsen. This experimental concept aims to monitor the shaft’s torque and thrust fluctuations during ice navigation to obtain information about the ship’s propulsion efficiency. In the paper, we describe the arrangement of the measurement system and the components it features. Finally, we present preliminary datasets acquired during two icebreaking expeditions. This work is framed into a broader research project, which includes the long-term objective to determine a correlation between sea ice conditions and the dynamic response of shaft lines.